Etika Bergaul Anak Muda Di Jakarta: Peran Pemikiran Ulama Nusantara Dalam Membangun Adab Di Era Digital - Muhammad Irfan Irfan; Rif'atul Hasanah; Ammar Ammar; Abdul Fadhil (Yayasan Al-Afif, 2025)
Youth interaction patterns in Jakarta have changed significantly with the development of technology and social media, presenting ethical challenges in communication. This study aims to explore how the thoughts of Nusantara scholars, with a moderate and contextual approach, can guide youth interaction ethics in the digital era. A descriptive qualitative method was used, involving in-depth interviews and literature studies. The findings show that values such as prudence in speech, self-control, and the ethics of the Prophet Muhammad are relevant in addressing issues like FOMO and communication style shifts. The study concludes that the teachings of Nusantara scholars can serve as an adaptive moral guide. It is recommended to integrate these values into digital education for youth.